JNK1 Mediates Lipopolysaccharide-Induced CD14 and SR-AI Expression and Macrophage Foam Cell Formation - An, Dong; Hao, Feng; Hu, Chen; Kong, Wei; Xu, Xuemin; Cui, Mei-Zhen (Frontiers in Physiology, 2018)
Foam cell formation is the key process in the development of atherosclerosis. The uptake of oxidized low-density lipoprotein (oxLDL) converts macrophages into foam cells. We recently reported that lipopolysaccharide (LPS)-induced foam cell formation is regulated by CD14 and scavenger receptor AI (SR-AI). In this study, we employed pharmaceutical and gene knockdown approaches to determine the upstream molecular mediators, which control LPS-induced foam cell formation. Our results demonstrated that the specific c-Jun N-terminal kinase (JNK) pathway inhibitor, SP600125, but neither the specific inhibitor of extracellular signaling-regulated kinase (ERK) kinase MEK1/2, U0126, nor the specific inhibitor of p38 MAPK, SB203580, significantly blocks LPS-induced oxLDL uptake, suggesting that the JNK pathway is the upstream mediator of LPS-induced oxLDL uptake/foam cell formation. To address whether JNK pathway mediates LPS-induced oxLDL uptake is due to JNK pathway-regulated CD14 and SR-AI expression, we assessed whether the pharmatheutical inhibitor of JNK influences LPS-induced expression of CD14 and SR-AI. Our results indicate that JNK pathway mediates LPS-induced CD14 and SR-AI expression. To conclusively address the isoform role of JNK family, we depleted JNK isoforms using the JNK isoform-specific siRNA. Our data showed that the depletion of JNK1, but not JNK2 blocked LPS-induced CD14/SR-AI expression and foam cell formation. Taken together, our results reveal for the first time that JNK1 is the key mediator of LPS-induced CD14 and SR-AI expression in macrophages, leading to LPS-induced oxLDL uptake/foam cell formation. We conclude that the novel JNK1/CD14/SR-AI pathway controls macrophage oxLDL uptake/foam cell formation.